1999
DOI: 10.1021/la980875f
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of Monovalent Electrolyte Ions on α-Alumina. I. Electroacoustic Studies at High Electrolyte Concentrations

Abstract: An electroacoustic technique has been used to monitor the binding of various monovalent inorganic ions on α-alumina at different pHs, nondilute solids, and moderate to high (0.01−1.0 mol dm-3) electrolyte concentrations. The ζ potential versus pH data show that NaNO3, KNO3, CsNO3, KBr, KCl, and KI are indifferent electrolytes for the α-alumina surface. However, LiNO3 causes a significant change in the isoelectric point of α-alumina, indicating that Li+ adsorbs in a specific manner to the surface over the range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
112
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(154 citation statements)
references
References 65 publications
39
112
2
1
Order By: Relevance
“…Previous studies have demonstrated preferential adsorption of Na þ over Cs þ ions on haematite and other metal oxide surfaces [27][28][29][30][31] . The ionic adsorption sequence: (refs 30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated preferential adsorption of Na þ over Cs þ ions on haematite and other metal oxide surfaces [27][28][29][30][31] . The ionic adsorption sequence: (refs 30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental measurements at high concentrations of various electrolytes (0.1 to 3 M) instead show that pH iep values increase with ionic strength for TiO 2 (anatase form), and ZrO 2 (55), as well as to a lesser extent with α-Al 2 O 3 (56). This is indicative of a stronger interaction of the electrolyte cation with these surfaces relative to the electrolyte anion.…”
Section: Surface Complexation Modelingmentioning
confidence: 97%
“…(20) and (21)). Another objective is to determine the effect of large quantities of adsorbed ions on the rheological behavior (yield stress) of silica and determine whether there is any correlation with the measured zeta potentials.…”
Section: Introductionmentioning
confidence: 94%
“…The vane is immersed in the suspension, and the torque is measured as a function of time as the tool is rotated at a slow constant rate (0.04 revolutions per minute). The torque response is monitored as a function of time and is simply related to the shear yield stress as detailed elsewhere (34)(35)(36).…”
Section: Yield Stressmentioning
confidence: 99%
See 1 more Smart Citation